(untitled) (Proceedings of the International Conference on Public Health, 2019)
Attitude is what influences all actions an individual undertakes in life. Young adult’s attitude on sexual reproductive health has proven to have a significant influence on their sexual health lifestyle and access to healthcare. Institutions of higher learning have put in place measures to ensure student have access to youth friendly services yet this has not been matched with students utilizing the various reproductive health services within the university. To fully understand students attitude towards uptake of reproductive health services, the current study grounded on the health belief model builds on previous researches examining on youth attitudes’ to sexual and reproductive health. Methodology: Reflecting on 178 structured questionnaire administered to undergraduate students in Kenyatta University. Results: This paper highlights how students’ attitude to ABC strategy influences uptake of reproductive health services. Results indicated that student had a negative attitude towards abstaining, nearly half had a positive attitude to being faithful to one partner. Chi square results revealed significant relationships between uptake of reproductive health services and students attitude to abstinence till marriage (p=0.014), attitude in condom use (p=0.005 Discussion: Findings also showed a positive attitude to condom use contrary to some literature on the use of condoms among youths. ABC strategy had a significant impact on uptake to reproductive health progammes. The study established that students’ attitude to the ABC strategy for protective sexual behaviour influenced uptake of reproductive health services. Conclusion: In light of these findings, the study recommends need for reproductive health programmes to redouble their efforts in strengthening the ABC strategy among university students in order to positively influence students’ sexual attitudes and behaviour.